Inputting ethical decision making framework from a commentary of Soorah Al-Hujuraat - Sulaiman, Mohamed; Karim, Khondaker Sazzadul; Mhd. Sarif, Suhaimi (The Journal of Academic Research on Management Accounting and Finance (JARMAF), 2013)
An absence of ethical decision-making by businesses can be understood as a problem of social judgment, which leads to an increase of misconduct at all levels. In this paper, the researchers investigated the ethical and leadership guidelines from the Soorah Al-Hujuraat and then tried to explore ethical business decision making process of management from a commentary of Soorah Al Hujuraat. A sample of six respondents was selected, two respondents were from university academicians of Qur'an and Sunnah Department and four respondents were from the different leading business organizations. From the respondents' view this can be highlighted that factors such as patience, controlling anger, equal opportunity and fairness, procedure for visits to another organization, conflict and dispute management, prohibition on the belittle, scoff, arrogance and backbiting practices, and Allah's consciousness can help managers and individuals of the organization to be more productive and harmonious in their interpersonal relationship. There were almost unanimous response among the respondents that the patience, anger management and the Prophet's teaching about business as the major contributors of the decision making process. As a way forward to improve on the ethical business decision making process, respondents suggested and felt the need of the training and knowledge sharing on the Prophet's teaching of business in the organization